Silibinin inhibits VEGF secretion and age‐related macular degeneration in a hypoxia‐dependent manner through the PI‐3 kinase/Akt/mTOR pathway. (24th January 2013) - Lin, CH; Li, CH; Liao, PL; Tse, LS; Huang, WK; Cheng, HW; Cheng, YW
<x xml:space="preserve">Abstract</x> Background and Purpose Hypoxia‐mediated neovascularization plays an important role in age‐related macular degeneration (AMD). There are few animal models or effective treatments for AMD. Here, we investigated the effects of the flavonoid silibinin on hypoxia‐induced angiogenesis in a rat AMD model. Experimental Approach Retinal pigmented epithelial (RPE) cells were subjected to hypoxia in vitro and the effects of silibinin on activation of key hypoxia‐induced pathways were examined by elucidating the hypoxia‐inducible factor‐1 alpha (HIF‐1α) protein level by Western blot. A rat model of AMD was developed by intravitreal injection of VEGF in Brown Norway rats, with or without concomitant exposure of animals to hypoxia. Animals were treated with oral silibinin starting at day 7 post‐VEGF injection and AMD changes were followed by fluorescein angiography on days 14 and 28 post‐injection. Key Results Silibinin pretreatment of RPE cells increased proline hydroxylase‐2 expression, inhibited HIF‐1α subunit accumulation, and inhibited VEGF secretion. Silibinin‐induced HIF‐1α and VEGF down‐regulation required suppression of hypoxia‐induced phosphatidylinositol 3‐kinase/Akt/mammalian target of rapamycin (mTOR) pathway. In the rat model of AMD, silibinin administration prevented VEGF‐ and VEGF plus hypoxia‐induced retinal oedema and neovascularization. Conclusion and Implications The effects of silibinin, both in vitro and in vivo, support its potential as a therapeutic for the prevention of neovascular AMD.